مستوى معرفة معلمي الثانوية بمهارات بناء الاختبارات التحصيلية وفق جدول المواصفات: دراسة استكشافية بثانويات المكلا النموذجية بمحافظة حضرموت الساحل - باوادي، سالم أحمد; بونمي، لينا جعفر; باني، نوال محفوظ (جامعة الريان, 2022)
تستهدف الدراسة التعرف إلى مستوى معرفة معلمي ثانويتي المكلا النموذجية بمحافظة حضرموت الساحل بمهارات بناء الاختبارات التحصيلية وفق جدول المواصفات وكذلك التعرف إلى الفروق في مستوى المعرفة بين محاور الدراسة تبعا لمتغير (التخصص، الخبرة، الجنس)؛ وتم استخدام المنهج الوصفي الاستكشافي. ولتحقيق أهداف الدراسة تم استخدام الاستبانة أداة للدراسة مكونة من (35) فقرة، موزعة على المحاور الثلاثة الآتية: (الغرض من الاختبار الأهداف التعليمية، الوزن النسبي)، وذلك بعد التأكد من صدقها وثباتها، وبلغ عدد أفراد مجتمع الدراسة (48) معلما ومعلمة، من معلمي ثانويتي المكلا النموذجية بمحافظة حضرموت الساحل، وتوصلت الدراسة إلى النتائج الآتية: أن مستوى معرفة معلمي ثانويتي المكلا النموذجية بمهارات بناء الاختبارات التحصيلية وفق جدول المواصفات عالية في جميع محاور أداة الدراسة الثلاثة، (الوزن النسبي، الأهداف التعليمية لموضوع المادة الدراسية، الغرض من الاختبار) على التوالي، كما لم تظهر فروق ذات دلالة إحصائية تعزى لمتغيرات (التخصص، والخبرة، والجنس). The study aimed to identify the level of knowledge of model secondary school teachers in the skills of constructing achievement tests according to a specification table, and to identify the differences in the level of knowledge between the axes of the study according to the variable (specialization, experience, gender) in Hadhramout Governorate- coast. The descriptive method was used to achieve the objectives of the study, a questionnaire was used after verifying its validity and reliability, consisting of (35) items distributed on the three axes (the purpose of the test, the educational objectives, the relative weight). The study population was (48) male and female teachers of the model secondary school in Hadhramout Governorate (Coast). The study reached the following results: The level of knowledge of model secondary school teachers in the skills of building achievement tests according to the specification table is high in all three axes of the study tool, (determining the relative weight, determining the educational objectives of the subject of the study, determining the purpose of the test) respectively. There were no statistically significant differences due to the study variables: (specialization, experience, gender).
Keywords: المؤسسات التعليمية -- التقويم -- الاختبارات التحصيلية -- التعليم الثانوي